Characteristics, Educational Preparation, and Membership In Professional Organizations of Agricultural Communicators - Cheryl A. Buck; Curtis E. Paulson (Journal of Applied Communications, 1995)
As the Profession of agricultural communication continues to develop and refine its mission in society, we must relate this mission to our academic programs.